Kunjungan Wisatawan dan Bisnis Kuliner di Kota Bandung - Sulaeman Rahman Nidar; Sutisna Sutisna; Egi Arvian Firmansyah (Ultima Management : Jurnal Ilmu Manajemen, 2018)
The city of Bandung is one of the cities which becomes a tourist destination for local and foreign tourists. This study explores the number of culinary business expected to increase the number of tourists visiting Bandung. The research was conducted using the survey method with culinary respondents of entrepreneurs or businesses, tourism office and tourists. This study aims to determine the influence or relationship between the number of culinary business and the number of tourists interested in culinary. Besides, this research aims to know the profile of tourists visiting Bandung. This research is descriptive and quantitative research. The results showed that the majority of tourists who come to Bandung are loyal tourists. They believe that culinary is one of the most interesting aspects of Bandung. In addition, statistically it is also known that the number of culinary entrepreneurs is positively correlated with the number of tourists who come to Bandung. The variable of the number of tourists can be explained by the variable number of culinary entrepreneurs, but not significant. Keywords: Bandung, Culinary Tour, Tourists